A cyano-bridged Cu(i)-based organic framework coupled with the C–C bond cleavage of acetonitrile for selective and sensitive sensing of Fe3+ ions. Issue 20 (30th April 2018) - Gai, Yanli; Zhao, Xueyan; Chen, Yan; Yang, Silei; Xia, Xinshu; Liu, Shan; Wan, Xiuyan; Xiong, Kecai
Abstract : A novel cyano-bridged Cu(i )-based organic framework, in which all cyano anions were generated in situ from the C–C bond cleavage of acetonitrile, exhibits a highly selective and sensitive sensing for Fe 3+ ions. Abstract : A cyano-bridged Cu(i ) organic framework based on [Cu6 (CN)6 ] n was synthesized, in which cyano anions were generated in situ from the C–C bond cleavage of acetonitrile. The as-synthesized compound displays orange-red luminescence and is further proven to be a promising Fe 3+ luminescent sensor with high selectivity and sensitivity.